A Conjugate Gradient Method for Discrete-Time Output Feedback Control Design (Journal of Computational Mathematics, 2012)
In this paper, the discrete-time static output feedback control design problem is considered. A nonlinear conjugate gradient method is analyzed and studied for solving an unconstrained matrix optimization problem that results from this optimal control problem. In addition, through certain parametrization to the optimization problem an initial stabilizing static output feedback gain matrix is not required to start the conjugate gradient method. Finally, the proposed algorithms are tested numerically through several test problems from the benchmark collection.